Practical Completion for Water Supply Projects - Jaffar, Khairi (2007)
Practical completion is a term used in the construction industry and many standard forms of contract to denote completion of the works by the Contractor. The law and practices in relation to the completion of building and engineering projects are complex issues that often give rise to conflict. There are only a few law cases that give guidance to practitioners. It seems that the meaning of practical completion is still not settled although the phrase has been used and found in many standard forms over the decades. This present the construction industries with uncertainty as to its exact meaning, leaving it open to various interpretations. The aim of this study is to determine legal meaning of practical completion and to develop a guideline that can assists in certifying practical completion particularly for water supply projects. For determining the legal meaning, the study focused on courtsâ€™ decisions in defining the terms of completion of works, provision in the standard forms, commentary from the learned authors and the practicalities of construction works itself. A guideline for certifying practical completion of water supply projects has been developed based on the issues found from the analysis of a few samples of completed water supply projects, practicalities and guided with the legal meaning as suggested. Based on the study, the writer suggested that the correct legal meaning of practical completion is â€œPractical completion occurs when the Works has reached such a stage of completion that they are capable of being occupied or used by the Employer for the purpose for which they are apparently required and intended, notwithstanding the presence of minor outstanding works and trivial defectsâ€?. From the proposed definition, it means that, for the Contract Administrator to exercise his opinion, what has to be considered is a particular criteria rather than an abstract and undefined concept; and the actual use of the works by the employer for the required purpose or intended will be prima facie evidence that the criteria has been met, regardless of the presence of minor outstanding works or trivial defects. It would thus be beneficial to the contracting parties if an unambiguous definition and guideline for certifying of practical completion is provided in the contract document. The Contractor may plan the works based on the intent of the contract so that principal areas will be ready for occupation or use by the due date for completion and some less critical outstanding works may be completed during the defects liability period.